2011
DOI: 10.1111/j.1462-2920.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Invariable biomass‐specific primary production of taxonomically discrete picoeukaryote groups across the Atlantic Ocean

Abstract: Oceanic photosynthetic picoeukaryotes (< 3 µm) are responsible for > 40% of total primary production at low latitudes such as the North-Eastern tropical Atlantic. In the world ocean, warmed by climate changes, the expected gradual shift towards smaller primary producers could render the role of photosynthetic picoeukaryotes even more important than they are today. Little is still known, however, about how the taxonomic composition of this highly diverse group affects primary production at the basin scale. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 41 publications
6
42
0
Order By: Relevance
“…The high Prymnesiophyceae signal detected across all ocean basins (Supplementary Table 3) supports the observation that 19 0 -hexanoyloxyfucoxanthin, a prymnesiophyte-specific pigment (though also present in a few other Heterokont algae, see Andersen, 2004), often dominates oceanic pigment analyses Liu et al, 2009). Recent fluorescent in situ hybridisation studies confirm the high abundance of these pico-prymnesiophytes in the Atlantic Ocean (Jardillier et al, 2010;Grob et al, 2011;Kirkham et al, 2011b), Indian Ocean and in open ocean regions of the Arctic Ocean . However, Prymnesiophyceae have been consistently underestimated in previous amplificationbased studies using primers targeting the nuclear 18S rRNA gene, potentially a result of PCR bias (Liu et al, 2009).…”
Section: Ppe B-diversitysupporting
confidence: 63%
See 2 more Smart Citations
“…The high Prymnesiophyceae signal detected across all ocean basins (Supplementary Table 3) supports the observation that 19 0 -hexanoyloxyfucoxanthin, a prymnesiophyte-specific pigment (though also present in a few other Heterokont algae, see Andersen, 2004), often dominates oceanic pigment analyses Liu et al, 2009). Recent fluorescent in situ hybridisation studies confirm the high abundance of these pico-prymnesiophytes in the Atlantic Ocean (Jardillier et al, 2010;Grob et al, 2011;Kirkham et al, 2011b), Indian Ocean and in open ocean regions of the Arctic Ocean . However, Prymnesiophyceae have been consistently underestimated in previous amplificationbased studies using primers targeting the nuclear 18S rRNA gene, potentially a result of PCR bias (Liu et al, 2009).…”
Section: Ppe B-diversitysupporting
confidence: 63%
“…Although there is a general trend in the PPE/total picophytoplankton (that is, PPEs þ picocyanobacteria) ratio increasing systematically with increasing latitude and decreasing temperature (Bouman et al, 2012), a considerable amount of variability is observed across the range of latitudes and temperatures. It is important to remember that even at very low cell abundances, PPEs are now known to contribute significantly to marine primary production because of a multifactorial effect of greater biovolume, higher growth rates and high grazing mortality rates (Li, 1994;Worden et al, 2004;Jardillier et al, 2010;Grob et al, 2011). Marine PPE community structure AR Kirkham et al PPE a-diversity Clone sequence data of the 16S rDNA from all the transects studied here (except the BEAGLE and Indian Ocean transects) representing 31 clone libraries allowed us to calculate species richness values (a-diversity) using the Margalef index (Dmg) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though photosynthetic picoplankton are dominated numerically by Prochlorococcus and Synechococcus, much of the carbon is fixed by photosynthetic picoeukaryotes such as the exceptionally diverse haptophytes (Grob et al, 2011). Picohaptophytes are thought to contribute 30-50% of the total photosynthetic standing stock across the world ocean with their competitive success attributed to their mixed mode of nutrition as some are able to photosynthesize as well as engulf bacteria (Liu et al, 2009).…”
Section: Ultraoligotrophic Ecosystemsmentioning
confidence: 99%
“…Yet, despite general descriptions of a deep layer of new production having been available for over 20 years, identification of the responsible organisms and explanations for the fate of the consumed NO 3 − remain equivocal. This is in part driven by our limited understanding of how factors other than slowly changing irradiance intensities impact the lower reaches of the euphotic zone (Letelier et al 2004, Dore et al 2008, Dave & Lozier 2010, but also by limited understanding of picoplankton community structure at depth (Fuller et al 2006, Worden & Not 2008, Grob et al 2011, Kirkham et al 2013.…”
Section: Introductionmentioning
confidence: 99%